Changes in students' goal pursuits and motivational regulations toward healthy behaviors during the pandemic: A Self-Determination Theory perspective. (March 2022) - Behzadnia, Behzad; Alizadeh, Elaheh; Haerens, Leen; Aghdasi, Mohammad Taghi
Abstract: Objectives: In this study, we examined how students' perceptions of teachers and parents' need-supportive and need-thwarting behaviors, related to their intrinsic and extrinsic goal pursuits, and in turn their motivational regulations toward physical activity in virtual physical education lessons over a semester during the Sars-COV2 pandemic. Design: Short-term longitudinal study. Methods: Students ( M age  = 14.43, SD  = 0.99) completed the targeted questionnaires at the beginning (T1, N  = 295) and the end (T2, N  = 194) of a virtual semester. Results: The results of the autoregressive model indicated that all measures were relatively stable from T1 to T2. Neither teachers nor parents' need-supportive and need-thwarting behaviors at T1 predicted students' intrinsic goal pursuits at T2, except for teachers' need-supportive behaviors at T1 negatively marginally predicted students' extrinsic goal pursuits at T2. The results also showed that intrinsic goal pursuits at T2 positively and negatively related to autonomous motivation and amotivation at T2, respectively. Extrinsic goal at T2 positively related to controlled motivation and amotivation at T2. Conclusions: Findings suggested that teachers need-supportive behaviors are important for decreasing students' extrinsic goal pursuits, while parents' need-thwarting behaviors relate to students' amotivation over time during the lockdown periods. Also, students' intrinsic goal pursuits would contribute positively to autonomous motivation and negatively to amotivation over time. Highlights: Neither teachers nor parents' need-supportive and need-thwarting behaviors predicted students' intrinsic goal pursuits over time. Teachers' need-supportive behaviors marginally negatively predicted students' extrinsic goal pursuits, but teachers' need-thwarting behaviors did not predict students' extrinsic goal pursuits. Parents' need-supportive and need-thwarting behaviors did not predict students' extrinsic goal pursuits. Parents' need-thwarting behaviors predicted students' amotivation over a semester during the Sars-COV2 pandemic. Students' intrinsic goal pursuits positively related to autonomous motivation and negatively to amotivation, whereas, students' extrinsic goal pursuits positively related to controlled motivation and amotivation.